2013
DOI: 10.1371/journal.pone.0081619
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Biological Activity of the Cystine Knot Bioinsecticide PA1b (Pea Albumin 1 Subunit b)

Abstract: The PA1b (Pea Albumin 1, subunit b) peptide is an entomotoxin extract from Legume seeds with lethal activity on several insect pests, such as mosquitoes, some aphids and cereal weevils. This 37 amino-acid cysteine-rich peptide has been, until now, obtained by biochemical purification or chemical synthesis. In this paper, we present our results for the transient production of the peptide in Nicotiana benthamiana by agro-infiltration, with a yield of about 35 µg/g of fresh leaves and maximum production 8 days af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…Pa1b has two internal Asn sites that represent putative processing sites of endogenous AEPs, thus Pa1b represents a good peptide to test for yield improvements in our ΔAEP N. benthamiana line devoid of AEP activity (Figure 5A). Similar to the PA1 expression results reported by Eyraud et al (2013), we found that PA1 expression in N. benthamiana results in a number of processed forms, with the predominant signals representing Pa1b with the C-terminal Gly37 removed, with or without oxidation (plus 16 daltons) of methionine residue. We found this similar pattern of processing in both wild type and ΔAEP plants; however relative yields were calculated to be ~3.7-fold and ~1.9-fold higher in ΔAEP plants for Pa1b-Gly and Pa1b-Gly+Met ox respectively (Figure 5B and C).…”
Section: Bioactive Linear Peptide Accumulationsupporting
confidence: 88%
See 1 more Smart Citation
“…Pa1b has two internal Asn sites that represent putative processing sites of endogenous AEPs, thus Pa1b represents a good peptide to test for yield improvements in our ΔAEP N. benthamiana line devoid of AEP activity (Figure 5A). Similar to the PA1 expression results reported by Eyraud et al (2013), we found that PA1 expression in N. benthamiana results in a number of processed forms, with the predominant signals representing Pa1b with the C-terminal Gly37 removed, with or without oxidation (plus 16 daltons) of methionine residue. We found this similar pattern of processing in both wild type and ΔAEP plants; however relative yields were calculated to be ~3.7-fold and ~1.9-fold higher in ΔAEP plants for Pa1b-Gly and Pa1b-Gly+Met ox respectively (Figure 5B and C).…”
Section: Bioactive Linear Peptide Accumulationsupporting
confidence: 88%
“…This peptide is of high interest for development as it represents the first ever peptide that specifically inhibits insect vacuolar proton pumps (Chouabe et al, 2011). Although produced naturally in many legumes, the development of Pa1b as a commercial insecticide would benefit from an expression platform allowing the rapid testing of variants for improved yield and potency, and with the capacity for scaled up production (Eyraud et al, 2013). Pa1b has two internal Asn sites that represent putative processing sites of endogenous AEPs, thus Pa1b represents a good peptide to test for yield improvements in our ΔAEP N. benthamiana line devoid of AEP activity ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…3 and Additional file 2 : Table S5). In this putative “nodulin” cluster, it is likely that the structural constraints for knotted peptide folding are released, which would fit with the absence of a PA1a moiety, as this domain is now strongly suspected of serving as a chaperone for assisted co-translational folding of most canonical PA1b peptides [ 51 ]. Since knottins are not all difficult to fold [ 52 ], the presence of a flanking pro-peptide chaperone is probably useful in a restricted part of the conformational space explored by the A1bs from Medicago truncatula .…”
Section: Discussionmentioning
confidence: 99%
“…Pea albumin 1 subunit b (PA1b) from pea and other legumes has been shown to have insecticidal effects on a range of pests and so may confer biological protection to the seed ( Louis et al, 2004 ). Six isoforms of PA1b exist in pea, five of which have shown similar insecticidal activity ( Eyraud et al, 2013 ). PA1b subunits are derived by post-translational modification of the product of PA1 genes ( Eyraud et al, 2013 ) and there are approximately eight PA1 genes ( Kreplak et al, 2019 ).…”
Section: Proteinmentioning
confidence: 99%
“…Six isoforms of PA1b exist in pea, five of which have shown similar insecticidal activity ( Eyraud et al, 2013 ). PA1b subunits are derived by post-translational modification of the product of PA1 genes ( Eyraud et al, 2013 ) and there are approximately eight PA1 genes ( Kreplak et al, 2019 ).…”
Section: Proteinmentioning
confidence: 99%